Paving the Path for Student Success -- It Is Not All About the Students! - Nasr, Payman; Jackson-Harris, Cheryl (Clinical Laboratory Science)
Academic success is a term that is often used to indicate student's ability to succeed in an academic environment and is primarily considered the product of students' dedication and commitment to their academic responsibilities. However, the faculties at California State University Dominguez Hills Clinical Laboratory Sciences Program have noticed a growing number of students, who despite of taking their academic responsibilities seriously are yet unable to graduate within the expected 4 years. California State University Dominguez Hills Clinical Laboratory Sciences is accredited by National Accrediting Agency for Clinical Laboratory Sciences and admits both undergraduate and post-baccalaureate candidates for training as Clinical Laboratory Scientists for careers in healthcare or research. Despite the great success in graduating well qualified candidates, there has been a trend in which a larger portion of students spend more than expected time to complete the program requirements. This phenomenon prompted the faculty to investigate the likely causes for lengthy graduation rate. Two student surveys were administered; the first survey was an online questionnaire that was emailed to all part-time and full-time Clinical Sciences Students who had declared their major as Clinical Laboratory Sciences (n=220) in spring 2015, while the second survey was only submitted in person to the students who had successfully entered the clinical internship program (n=43) during the same year with the main goal being to establish the strengths and weaknesses of the program from the students' perspective who are about to complete the program requirement and earn their certification. The rate of response for the first survey was 27.7%, while the second survey response rate was 100%. The analysis revealed a number of causes for prolonged rate of graduation; however by far, the findings suggest the primary cause to be challenges associated with registration in required courses due to personal schedule conflicts and/or intense competition for available seats.